Principal components approach of physiological and physical metrics collected through GPS technology in soccer referees - Castillo-Rodríguez, A.; Onetti-Onetti, W.; Manuel Clemente, F.; Tomás González-Fernández, F. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
The aim of this study was to define and classify the different physical and physiological performance metrics on national and non-national soccer referees (SRs) through GPS technology. Sixty SRs (age: 28.9 ± 4.9 years; weight: 70.2 ± 8.0 kg; height: 175.7 ± 5.5 cm) were tested using the 18 Hz global positioning system (GPS) (WimuPro, Realtrack, Almería, Spain). An exploratory factor analysis was performed using principal component analysis (PCA) on performance indicators with orthogonal rotation (VariMax). Thirteen metrics (total distance, distance covered at different speeds, maximum heart rate, and heart rate recorded in different zones) were integrated in three principal components, activation (PCA1), recovery (PCA2), and high intensity (PCA3). They represented 86% and 89% of total explained variance of the competition performance in national and non-national SRs, respectively. Distance covered at very high speed and heart rate between 80% and 89.9% of the maximum integrated the high-intensity principal component and were higher in non-national SRs. The main finding of this study was that it defined for the first time in the scientific literature the main components that discriminate physical performance between national and non-national referees, where high intensity metrics have greater weight in non-national referees. In addition, GPS technology together with PCA analysis were presented as useful methods to discriminate the most representative physical and physiological performance metrics in sports competition in SRs.